2016
DOI: 10.1111/1467-9817.12092
|View full text |Cite
|
Sign up to set email alerts
|

Derivational suffixes as cues to stress position in reading Greek

Abstract: Background In languages with lexical stress, reading aloud must include stress assignment. Stress information sources across languages include word‐final letter sequences. Here, we examine whether such sequences account for stress assignment in Greek and whether this is attributable to absolute rules involving accenting morphemes or to probabilistic lexical information. Methods Pseudowords were constructed to not resemble particular words and were suffixed with derivational morphemes associated with specific s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 49 publications
3
6
0
1
Order By: Relevance
“…The effect of suffix frequency on the reading accuracy of children, and of children with dyslexia in particular, must have its source on some properties of suffixes in driving pronunciation after starting the pronunciation process. It has been often shown in developmental reading studies that suffixes act as stress attractors (e.g., Jarmulowicz et al, 2007 , 2008 ) and more generally provide a cue to stress position, i.e., to where stress should be placed when pronouncing a word ( Grimani and Protopapas, 2017 ). This is crucial in pronouncing polysyllabic words like Italian derived words, which are usually 3-to-5 syllables long.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of suffix frequency on the reading accuracy of children, and of children with dyslexia in particular, must have its source on some properties of suffixes in driving pronunciation after starting the pronunciation process. It has been often shown in developmental reading studies that suffixes act as stress attractors (e.g., Jarmulowicz et al, 2007 , 2008 ) and more generally provide a cue to stress position, i.e., to where stress should be placed when pronouncing a word ( Grimani and Protopapas, 2017 ). This is crucial in pronouncing polysyllabic words like Italian derived words, which are usually 3-to-5 syllables long.…”
Section: Discussionmentioning
confidence: 99%
“…However, each of these alternative orthographic units contained fairly reliable cues to stress indicating the presence of multiple cues. Subsequent behavioral and electrophysiological studies have demonstrated participants' sensitivity to these kinds of probabilistic orthographic cues in languages other than English (e.g., see studies of Italian, Greek, and Russian by Burani & Arduino, 2004;Grimani & Protopapas, 2017;Jouravlev & Lupker, 2014Sulpizio & Colombo, 2017, among others).…”
Section: Lesser-known Regularities That Help Us Assign Lexical Stress When Reading Aloudmentioning
confidence: 99%
“…In our study (Grimani & Protopapas, 2009) we focused on derivational morphemes thought to constrain stress, such as -οσύνη /osini/ and -ότητα /otita/ (both meaning -ness/-ity, e.g., καλοσύνη /kaloˈsini/ "kindness", χρησιµότητα /xrisiˈmotita/ "usefulness"). The former bears penultimate-syllable stress whereas the latter bears antepenultimate-syllable stress.…”
Section: Sources Of Stress Informationmentioning
confidence: 99%